Kundalini Yoga: From the Early Tantras To the Hatha Yoga - Yudiantara, Putu (DHARMASMRTI: Jurnal Ilmu Agama dan Kebudayaan, 2025)
This article presents a historical review of the conceptualization of Kundalini and Kundalini Yoga within Tantric texts from the 7th to the 12th centuries and tracing their continuity in Hatha Yogic literature. Its objective is to analyze the persistence and development of conceptual elements over time and to investigate key themes elucidating the ontological and practical dimensions of Kundalini and Kundalini Yoga. The findings reveal that early Tantric texts portray Kundalini as a cosmogonic and mantric force, while Kun?d?alin? Yoga practices entail the utilization of mantras in conjunction with breath control techniques. In Hatha Yogic texts, Kundalini undergoes a transformation from a cosmogonic force to a personal energy intrinsic to individuals and subjects to physical manipulations. This study underscores the significance of contextualizing Kundalini within its philosophical and spiritual framework, often overlooked in mainstream culture or studies concentrating solely on its physical manifestations.